(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Present investigation was conducted during 2021 at Agricultureal Research Farm of Rama University , Mandhana, Kanpur (U.P), Studies on the“Efficacy of bio-fertilizer and the combinations with chemical fertilizers on chemical parameters of okra [Abelmoschus esculentus (L.) Moench]”, revealed that Acidity, Ascorbic acid and moisture percent were maximized. when we use with Recommended dose of fertilizers , NPK 40 percent, PSB 40 percent, Azotobacter 40 percent and Azospirillum 65 percent.